Effectiveness of lavender and lemon aromatherapy on postpartum perineal wound pain - Cahaya Indah Lestari; Mufdlillah (Alma Ata University Press, 2026)
Background: The maternal mortality rate in Indonesia remains above the World Bank’s estimated average. Various studies have been conducted to reduce this figure. One such study involves providing aromatherapy to postpartum mothers. Perineal pain is a frequently reported concern after childbirth, which can interfere with a mother’s recovery. The use of lavender and lemon aromatherapy offers a non-pharmacological therapeutic alternative for managing this discomfort. Objectives: This study aims to evaluate the effectiveness of lavender and lemon aromatherapy on postpartum perineal wound pain. Methods: The research design used was a pre-experimental study involving two experimental groups. The population in this study consisted of 40 postpartum mothers. Using a purposive sampling technique, 30 women were selected as the research sample. The instrument used was a VAS questionnaire with 4 response scales. Data were analyzed using a paired t-test and Cohen’s d. Results: The results revealed that lavender aromatherapy was effective in reducing postpartum perineal wound pain with moderate (2 hours) and severe (4 hours) criteria. This finding was attributed to lavender aromatherapy’s neuromodulatory effect, which impacted the psyche and caused mild anti-inflammatory effects on the wound. In fact, lemon aromatherapy proved effective with very severe criteria, both for the first 2 hours and the following 24 hours. These results were due to the combination of limbic neurotransmitters with peripheral anti-inflammatory effects, which helped mothers manage stress and other psychological factors during labor. Conclusions: The study concluded that lemon aromatherapy was more effective than lavender because it was richer in citric acid and limonene. The study recommended that future research use a larger sample size and include several covariates to ensure broad generalizability of the findings.